Students Insight on Internet Usage: A Study - Mani Kumar, M.; Karapudi, Basavaraja (Journal of Information and Knowledge, 2012)
The main objective of this paper is to examine the use of internet by the students of IBS-Bangalore, in order to determine the level usage, the major purpose behind accessing the internet and the required search strategy and information literacy skills to use Internet. The study reveals that usage of internet is very high among the students of ICFAI Business School.